MENGGUGAH KESADARAN SOSIAL DAN EMPATI PARA SISWA TERHADAP PERSOALAN SOSIAL DI LUAR KELAS - Weruin, Urbanus Ura (Jurnal Serina Abdimas, 2024)
The most basic aim of education is not only to develop students' cognitive abilities in mastering science, technology and the skills needed for life but also to develop character and personality that is moral, has noble character, acts in solidarity, is tolerant and cares about one's own interests. each other, and society as a whole. One of the characteristics and personalities of students that we want to produce through the education and learning process at school is the development of social awareness and empathy for social problems that exist in society. Social awareness is an understanding, attitude and appreciation of the existence of other people in wider society. Empathy is a form of social awareness. Social awareness and empathy in practice are nothing more than thinking about others. Education and learning about social awareness and empathy is a form of social responsibility as a citizen. Social awareness education and learning can stimulate students' social awareness and empathy. The vision and mission of SMA Bhinneka Tunggak Ika Jakarta, which emphasizes character education, needs to remind their students about social awareness and empathy towards others through this PKM. Mitra admits that their students often don't care about the social problems that exist in society. By using a problem-based learning approach and the 6D PKM learning method, it is able to stimulate and develop social awareness and sensitivity towards other people. This PKM succeeded in making students aware of social problems in the local and global scope that need to be the center of their attention. These problems range from sexual harassment, pollution, increasing pollution, and still high levels of collusion, corruption and nepotism, climate change due to increasing earth temperatures, wars between nations, and human tragedies resulting from wars that need their social attention. Education of students' social moral awareness and empathy is able to stimulate students' social awareness and empathy.